Fears of happiness and compassion in relationship with depression, alexithymia, and attachment security in a depressed sample. (27th November 2013) - Gilbert, Paul; McEwan, Kirsten; Catarino, Francisca; Baião, Rita; Palmeira, Lara
<x xml:space="preserve">Abstract</x> Objectives In a non‐clinical population, fears of compassion and fear of happiness have both been found to be highly correlated with alexithymia and depression. This study sought to explore these processes and their links with adult attachment and social safeness and pleasure in a depressed group. Method A total of 52 participants suffering from moderate to severe depression completed measures of fears of happiness, compassion from others and for self, in addition to measures of alexithymia, attachment, social safeness, and depression, anxiety, and stress. Results Fears of compassion and happiness were highly correlated with alexithymia, adult attachment, and depression, anxiety, and stress. Fear of happiness was found to be the best predictor of depression, anxiety, and stress, whereas fear of compassion from others was the best predictor of adult attachment. A path analysis showed that fears of positive emotion fully mediate the link between alexithymia and depression. This clinical sample had higher mean scores in fears of positive emotions, alexithymia, and depression, anxiety, and stress than a previously studied student sample. Conclusions This study adds to the evidence that fears of positive emotions are important features of mental health difficulties. Unaddressed, these fears can block positive emotions and may lead to emotional avoidance of positive affect thus contributing as blocks to successful therapy. Therapies for depression may therefore profitably assess and desensitize the fear of positive emotions. Practitioner points Many therapies focus on reducing negative affect and increasing positive affect. However, clinicians should be aware that positive emotions can be feared: in this clinical sample, depression is strongly associated with fear of happiness and fears of compassion. If clients fear happiness and compassion, they may resist or have difficulties in engaging in activities which evoke positive affect. If not addressed these fears may become blocks to therapy. Fears of different types of positive affect may require different interventions.